2021
DOI: 10.3390/jcm10112224
|View full text |Cite
|
Sign up to set email alerts
|

GamblingLess: A Randomised Trial Comparing Guided and Unguided Internet-Based Gambling Interventions

Abstract: There is little evidence relating to the effects of adding guidance to internet-based gambling interventions. The primary aim was to compare the effectiveness of an online self-directed cognitive-behavioural gambling program (GamblingLess) with and without therapist-delivered guidance. It was hypothesised that, compared to the unguided intervention, the guided intervention would result in superior improvements in gambling symptom severity, urges, frequency, expenditure, psychological distress, quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 104 publications
(188 reference statements)
1
20
0
Order By: Relevance
“…Furthermore, we had to deal with a large number of non-completers as only 43% completed the post assessment and replacement of missing values always results in a reduced statistical power. Other studies on Internet-based interventions for pathological gambling report a wide range of completion rates, ranging from 17 to 90% 25 30 , with several below 50% 26 , 28 , 29 . Accordingly, our completion rate can be considered comparable to similar studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we had to deal with a large number of non-completers as only 43% completed the post assessment and replacement of missing values always results in a reduced statistical power. Other studies on Internet-based interventions for pathological gambling report a wide range of completion rates, ranging from 17 to 90% 25 30 , with several below 50% 26 , 28 , 29 . Accordingly, our completion rate can be considered comparable to similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…Results regarding the superiority of guided over purely self-guided programs for gambling problems, however, are not that clear. One study compared self-guided iCBT with guided iCBT (e-mail guidance) and found no difference in effectiveness between groups; both led to a significant reduction in gambling symptom severity, urges, frequency, expenditure and psychological distress at 2- and 3-month follow-up, but the guided iCBT also resulted in significant improvements in quality of life and had higher rates of clinically significant changes 28 . Another study investigating different forms of Internet-based interventions in a sample of individuals with gambling problems found no difference in changes of gambling symptom severity of a guided form compared to an unguided one 29 .…”
Section: Introductionmentioning
confidence: 99%
“…GamblingLess [ 42 ] is a comprehensive and intensive web-based CBT program designed to help people with gambling problems. It was designed to emulate the intensity and depth of the face-to-face programs.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we describe the formative research that was an integral part of developing a mobile app for gambling harm for use in New Zealand: Manaaki. Specifically, we aim to (1) adapt and refine an evidence- and web-based program, GamblingLess [ 40 - 42 ], into a mobile app intervention and (2) engage domain experts and intended end users to help inform the content conversion and the design, features, and functions of the app and maximize the effectiveness of the program. This study is part of a larger project to evaluate the effectiveness of this designed cognitive behavioral therapy (CBT) mHealth intervention—Manaaki—for people with self-reported gambling problems [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first promising technology was virtual reality (VR), which emerged as a viable and effective tool for psychological disorders, reporting efficacy in the treatment of GD and the ERP component [ 27 , 28 , 29 , 30 ]. Furthermore, media development has led to the use of the internet to deliver CBT, obtaining adequate results in randomized control trials (RCT) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The efficacy of these self-guided treatments has been confirmed in many countries by scoping and systematic reviews or meta-analyses [ 14 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%